Proof of concept: Shape-sensing robotic-assisted bronchoscopy performed under moderate sedation. (2023) - Donna, Elio; Wu, Steven; Arias, Sixto
Abstract: We describe a first reported case of shape-sensing robotic-assisted bronchoscopy using ION-intuitive platform done successfully under moderate sedation. A 76-year-old woman was found to have a right upper lobe mass measuring 3 × 2.9 cm. Diagnostic robotic navigational bronchoscopy was successfully performed under moderate sedation. Pathologic examination later revealed adenocarcinoma consistent with primary pulmonary malignancy. Conscious sedation allows the use of robotic bronchoscopy with minimal CT-to-body divergence and systems error. Robotic bronchoscopy under moderate sedation is feasible and seems to be safe and can be done without immediate complications.